Human health risk assessment and carcinogenicity due to exposure to potentially toxic elements on soil pollution in Southwest Iran - Sara Mansouri Moghadam; Khoshnaz Payandeh; Azita Koushafar; Mohiaddin Goosheh; Maryam Mohammadi Rouzbahani (Elsevier, 2024)
Background: /objectives: Potentially toxic elements (PTEs) are one of the dangerous pollutants in the environment that can cause morbidity and mortality in humans. This study was designed to evaluate the concentration of PTEs, assessment its human health risk assessment and carcinogenicity in the north of Ahvaz, the southwest of Iran. Methods: The soil samples were collected from the agricultural fields and riversides for investigating the health effects of the selected PTEs on the soil of the Weiss and Arab Assad regions in Ahvaz. Results: According to the result of this study, the highest level of Fe was observed in the soil samples of the Weiss and Arab Assad regions, 9013.70 and 9208.93 mg/kg, while Cd showed the lowest concentration in the soils of Weiss and Arab Assad fields, 1.58 and 1.56 mg/kg, respectively. Potentially toxic elements hazard quotient (HQ), non-carcinogenic risk (HI), and risk index (RI)) in the soil of agricultural fields in the Arab Assad and Weiss regions showed that Cd, Pb, Ni, Cu, Cr, Zn, Fe, Mn, and Co posed a significant risk to human health. Thus, it is recommended to observe health issues due to the non-carcinogenic risk index of metals. Conclusion: Generally, the excessive use of agricultural fertilizers (phosphate and nitrate), industrial, and human activities can increase the contamination of the resources and products, which has irreversible effects on human health, especially in carcinogenic risk.